Intracellular delivery of messenger RNA to macrophages with surfactant-derived lipid nanoparticles - Y. Huang; M. Yang; N. Wang; S. Li; Z. Liu; Z. Li; Z. Ji; B. Li (Materials Today Advances, 2022)
The broad biomedical applications of messenger RNA (mRNA)-based therapeutics rely heavily on the rapid development of mRNA delivery systems. In this study, dual-component lipid nanoparticles (LNPs) were developed for intracellular delivery of mRNA to macrophages. By screening a panel of quaternary ammonium compounds with varying alkyl or aryl side chains, a cationic surfactant containing two hexadecyl tails was found to be effective for mRNA delivery with the assistance of fusogenic lipids. Further investigating structure alterations and optimization of formulation parameters, we found that a surfactant-derived ionizable lipid mixed with a fusogenic lipid was capable of condensing mRNA and self-assembling into LNPs. Without using the PEGylated lipid, the resulting LNPs were able to render the exogenous mRNA resistant to hydrolysis by nucleases and displayed excellent biocompatibility, along with the capacity to deliver mRNA to hard-to-transfect. Overall, the dual-component nanocarrier provides a novel mRNA delivery platform for genetic engineering of macrophages.